Analysis of the Geometric Thinking Stage of Madrasah Tsanawiyah Students Based on Van Hiele's Theory - Nasifah; Arif Muchyidin; Muhamad Ali Misri (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
In the process of learning mathematics, especially geometry, teachers must pay attention to the level of ability possessed by students. Van Hiele suggests that there are five stages of thinking that students will go through in learning geometry: the visualization stage, the analysis stage, the informal deduction stage, the deduction stage, and the rigor stage. Each stage of thinking will be passed by students sequentially without passing any of the previous stages. This study aimed to identify and describe the geometric thinking stages of high school students. The first is based on van Hiele's theory. The research method used in this research is descriptive quantitative. This research was conducted at MTs (Madrasah Tsanawiyah) An-Nur, Cirebon City, with a population of 318 students and a sample of 72 students selected using a purposive sampling technique. The data collection technique used is in the form of a Van Hiele geometric thinking stage test with 25 multiple choice questions divided into five subtests. The results showed that 29.17% of students were in stage 1 (visualization), 25% of students were in stage 2 (analysis), and 6.94% of students were in stage 3 (informal deduction). There are still students who have not entered the van Hiele geometric thinking stage (at stage 0), namely 13.89%. As for the students who could not determine their van Hiele geometric thinking stage, as many as 25%. The highest stage achieved by students was stage 3 (informal deduction), so no student reached stage 4 (deduction) and stage 5 (rigor). In general, the geometric thinking stage of MTs (Madrasah Tsanawiyah) An-Nur students is at stage 1 of van Hiele's geometric thinking.